An investigation of barriers affecting the use of simulation in the high school design process - Mathabatha, Lekoba Noria (My University, 2020)
This research focused on the effective use of simulation in the high school design process. Technology develops learners’ simulation skills in the design process. According to the CAPS document in technology, learners should be provided with the opportunities to use a variety of life skills to solve technological problems. Solving technological problems require learners to engage their simulation skills. This involves learners identifying problems, formulating problems, collecting real data, formulating and developing a model, validating the model, and documenting the model. Technology as a subject considers simulation skills as important to learners in real situations. It seems that teachers find it difficult to use simulation effectively in the classroom. The literature also reports that technology teachers fail to develop learners’ opportunities to handle the problems in the way of the goals that they need to achieve. This is a challenge in the teaching of technology. The study thus sought to investigate this challenge. This study used Maria’s (1997) simulation models: problem identifying, problem formulating, collecting data, developing model, validate model and documenting model. The study was also based on the design process, which includes: investigate design, make, evaluate and communicate. Maria’s simulation models were used with the design process to demonstrate the way in which simulation skills can be used to solve technological problems using the design process. This study engaged qualitative research using a multiple case study design and purposive sampling. Technology teachers with less than five years and those with more than five years of experience teaching technology were considered appropriate for this study. Data was collected by means of observations and semi-structured interviews and was analysed using the simulation models. A major finding of the study was that the technology teachers had inadequate knowledge of the use of simulation. The sampled technology teachers were unable to provide learners with opportunities to use simulation effectively in their classrooms. During the classroom observations, the participants did not engage the design process in the teaching of simulation. It appeared that these teachers were not aware of the requirements of CAPS. CAPS in technology stipulates that teachers should be aware that learners need to have knowledge of the design process (DBE, 2011). The major recommendation of this study is that technology teachers should have adequate knowledge of the use of simulation, the skills to be used in the use of simulation, and the steps to be used in gaining problem-solving skills. It is also recommended that technology teachers should ensure that they use the design process in the teaching of simulation. The use of the design process may provide teachers with opportunities to use simulation effectively in the classroom. Key words: Simulation, design process, problem solving skills, self-efficacy
Thesis (M. Ed. (Technology Education)) -- University of Limpopo, 2020
Keywords: Simulation; Design process; Problem solving skills; Self-efficacy; Curriculum-based assessment -- South Africa; Educational technology